Atypical ATMs: Broadening the phenotypic spectrum of ATM-associated hereditary cancer - Borja, Nicholas A.; Silva-Smith, Rachel; Huang, Marilyn; Parekh, Dipen J.; Sussman, Daniel; Tekin, Mustafa (Frontiers in Oncology, 2023)
Heterozygous, loss-of-function germline variants in ATM have been associated with an increased lifetime risk of breast, pancreas, prostate, stomach, ovarian, colorectal, and melanoma cancers. We conducted a retrospective review of thirty-one unrelated patients found to be heterozygous for a germline pathogenic variant in ATM and identified a significant proportion of patients in this cohort with cancers not currently associated with the ATM hereditary cancer syndrome, including carcinomas of the gallbladder, uterus, duodenum, kidney, and lung as well as a vascular sarcoma. A comprehensive review of the literature found 25 relevant studies where 171 individuals with a germline deleterious ATM variant have been diagnosed with the same or similar cancers. The combined data from these studies were then used to estimate the prevalence of germline ATM pathogenic variants in these cancers, which ranged between 0.45% and 2.2%. Analysis of tumor sequencing performed in large cohorts demonstrated that the frequency of deleterious somatic ATM alterations in these atypical cancers equaled or exceeded the alteration frequency in breast cancer and occurred at a significantly higher rate than in other DNA-damage response tumor suppressors, namely BRCA1 and CHEK2. Furthermore, multi-gene analysis of somatic alterations in these atypical cancers demonstrated significant co-occurrence of pathogenic alterations in ATM with BRCA1 and CHEK2, while there was significant mutual exclusivity between pathogenic alterations in ATM and TP53. This indicates that germline ATM pathogenic variants may play a role in cancer initiation and progression in these atypical ATM malignancies, potentially influencing these cancers to be driven toward DNA-damage repair deficiency and away from loss of TP53. As such, these findings provide evidence for broadening of the ATM-cancer susceptibility syndrome phenotype to improve the recognition of affected patients and provide more efficacious, germline-directed therapies.